PENGARUH MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - Rodotul Janah; Muhammad Hayun (STKIP Subang, 2026)
This study aims to determine the effect of the Value Clarification Technique (VCT) learning model on students' critical thinking skills in the Pancasila Education subject in elementary schools. The background of the study is based on observation findings at SDN Cilandak Barat 07 which showed that students' critical thinking skills were still low and learning tended to use conventional methods. This study used a quantitative approach with a Quasi Nonequivalent Control Group design experimental method. The study population was all 42 fifth-grade students, with class 5A (21 students) as the experimental group receiving the VCT model treatment and class 5B (21 students) as the control group with the conventional model. The sampling technique used purposive sampling. Data were collected through pretests and posttests in the form of essay questions. The results showed that the average posttest score of the experimental class (70.55) was higher than that of the control class (62.2). Hypothesis testing using an independent sample t-test yielded a significance value of 0.011 (<0.05), and a paired sample t-test yielded a significance value of 0.000 (<0.05), indicating a significant effect of the VCT model on students' critical thinking skills. The VCT model encourages students to be more active in analyzing problems, evaluating values, and drawing conclusions. Therefore, the VCT model is recommended as an effective learning alternative to improve students' critical thinking skills in Pancasila Education in elementary schools.